2016
DOI: 10.1002/ccd.26690
|View full text |Cite
|
Sign up to set email alerts
|

Long sheath use in femoral artery catheterizations in infants <15 kg is associated with a higher thrombosis rate

Abstract: The use of a long sheath in infants <15 kg is a significant risk factor for arterial compromise compared to short sheaths. Lower patient weight is also a contributing factor to increased incidence of complication, particularly in those <5 kg. © 2016 Wiley Periodicals, Inc.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 12 publications
0
22
0
Order By: Relevance
“…We also afford more consistency in procedure technique and patient management as a single‐center evaluation compared to their six site survey across multiple countries. Loose definitions of arterial thrombosis are also used in previous studies, with the majority of documented thromboses based on pulse loss or liberal definitions including many mechanisms of vascular compromise . By selecting US visualization of thrombosis as our primary definition of documented thrombosis, this affords less chance for false positive findings of thrombosis and less variability in reporting between patients in our population.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We also afford more consistency in procedure technique and patient management as a single‐center evaluation compared to their six site survey across multiple countries. Loose definitions of arterial thrombosis are also used in previous studies, with the majority of documented thromboses based on pulse loss or liberal definitions including many mechanisms of vascular compromise . By selecting US visualization of thrombosis as our primary definition of documented thrombosis, this affords less chance for false positive findings of thrombosis and less variability in reporting between patients in our population.…”
Section: Discussionmentioning
confidence: 99%
“…Postcatheterization femoral arterial thrombosis in infants can result in acute limb loss and long‐term consequences including leg‐length discrepancy and difficulty obtaining vascular access in future procedures . Younger age, lower weight, and larger catheters have been reported as factors associated with increased thrombotic risk . Using standard clinical detection methods, prior studies have demonstrated a range of femoral arterial thrombosis rates from 0.3 to 9.6% .…”
Section: Introductionmentioning
confidence: 99%
“…This difficulty is exacerbated by the tortuous nature of ductus arteriosus in these patients . In addition, long sheath use in femoral artery catheterizations in infants <15 kg are associated with higher thrombosis rates …”
Section: Introductionmentioning
confidence: 99%
“…The vertical and tortuous ductus has been a risk factor for procedural failure especially with a femoral approach due to the acute angle of the wire course. Long femoral sheaths have also been found to be a major risk factor for femoral artery occlusion in this population . This then led some centers to explore carotid access for these procedures as the ductus arteriosus would be more in line.…”
Section: Discussionmentioning
confidence: 99%